Аналіз ризиків кредитування галузей як інструмент антикризових заходів - Любіч, О.О.; Домрачев, В.М. (Економіка промисловості, 2012)
Здійснено аналіз ефективності кредитування банками окремих галузей економіки та галузевих ризиків банків України, виявлено залежність прибутку банку від частки кредитів у галузь у кредитному портфелі. Ключові слова: галузевий ризик, комерційні банки, кредитування підприємств галузі. Проведен анализ эффективности кредитования банками отдельных отраслей экономики и отраслевых рисков банков Украины, выявлена зависимость прибыли банка от доли кредитов в отрасль в кредитном портфеле. Ключевые слова: отраслевой риск, коммерческие банки, кредитование предприятий отрасли. This paper describes the effectiveness of ban lending analysis of individual industries, dependence on bank profits in the sector of loans in the loan portfolio. A financial crisis did not decrease imbalances in the Ukrainian banking system, as well as in a world economy in general.On the other hand, the current stage of inflation of bubbles was completed in the markets of speculative assets of Ukraine. Is there a question in banks – whom to credit? The resource base of banks grows; resources must be invested in profitable assets, in particular, credits. That is why for banks it becomes an actual question to analyze risks of crediting for particular economy branch taking into account the competitiveness of industries. The purposes of the articleare: to analyze the risks of crediting of separate industries of the Ukrainian economy; to offer the methods of bank estimation of risks of crediting of separate industries of Ukrainian economy; to define the possible ways of solutionof the question of economy crediting renewal by banks. Providing financial stability, which needs system approach to all constituents of the financial system in their co-operation and under the influence of the external factors generated by the processes of globalization, is the key condition of the permanent economic growth of Ukraine. Objective estimation of the risks related to the influence of threats on financial stability of the state is the urgent task. The connection of commodity flows and proper cash flows between branches of economy is the important factor of economic growth. The lack of credit resources in certain industry can result in confusions in this industry. During the crisis the considerable change in risks of crediting of separate industries took place in Ukraine. It is needed to decide, which industries is expedient to support: which suffered the most owing to crisis, or which are strategically more important, or which are the most profitable. Except the principle solution of strategic aims of industries development, it is necessary to estimate the effectiveness of possible application of instruments of anti-crisis measures, and decide on due to whom to provide industries with financial resources (for example, by the change of the tax policy or due to the introduction of state-private partnership). Consequently, the dynamics of decline in production in separate industries does not coincide with the factors of credit risk, which influence on income and interest return of banks. The most profitable industries do not use the credit resources of banks in proper volume. Keywords: industry risk, commercial banks, industry crediting.